Lithium-containing 45S5 Bioglass-derived glass-ceramics have antioxidant activity and induce new bone formation in a rat preclinical model of type 1 diabetes mellitus - Gomez Gramajo, Fátima; Rivoira, María A.; Rodríguez, Valeria; Vargas, Gabriela; Vera Mesones, Rosa; Zago, María P.; Boccaccini, Aldo R.; Gorustovich, Alejandro (Biomedical Materials, 2024)
Diabetes mellitus (DM) has been associated with complications that affect the skeletal system, such as alterations in bone repair, osteoporosis, and an increased risk of fractures. In this context, the use of biomaterials able to promote osteogenic differentiation and, at the same time, limit the oxidative stress induced by DM offers a novel perspective to ensure the repair of diabetic bone tissue. Since lithium (Li) has been recently identified as a biologically active ion with osteogenic and antioxidant properties, the localized and controlled release of Li ions from bioactive glass-ceramic materials represents a promising therapeutic alternative for the treatment of bone lesions in DM. Thus, the aim of this study was to evaluate the potential osteogenic and antioxidant effects of glass-ceramic microparticles derived from a 45S5-type bioactive glass (Bioglass) containing (% by weight) 45% SiO2, 24.5% Na2O, 24.5% CaO, and 6% P2O5, in which Na2O was partially substituted by 5% of Li2O (45S5.5Li), in an experimental model of type 1 DM (DM1). The results obtained demonstrate, for the first time, that both 45S5 and 45S5.5Li glass-ceramic microparticles possess antioxidant activity and stimulate bone formationin vivoboth under physiological conditions and under experimental DM1 in rats. In this sense, they would have potential application as inorganic osteogenic agents in different strategies of bone tissue regenerative medicine.
CRIS-Team Scopus Importer:2025-02-04
Keywords: antioxidant activity; bioactive glass-ceramics; bone repair; diabetes mellitus